2010
DOI: 10.1242/jcs.063222
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis DJ-1a protein confers stress protection through cytosolic SOD activation

Abstract: SummaryMutations in the DJ-1 gene (also known as PARK7) cause inherited Parkinson's disease, which is characterized by neuronal death. Although DJ-1 is thought to be an antioxidant protein, the underlying mechanism by which loss of DJ-1 function contributes to cell death is unclear. Human DJ-1 and its Arabidopsis thaliana homologue, AtDJ-1a, are evolutionarily conserved proteins, indicating a universal function. To gain further knowledge of the molecular features associated with DJ-1 dysfunction, we have chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
101
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 62 publications
4
101
1
Order By: Relevance
“…It was previously reported that endogenous AtDJ-1 level in leaf was increased after treatment with stress factors, such as strong light, H 2 O 2 , methyl viologen and copper sulfate. 23 DJ-1 supports the cellular redox homeostasis by subserving a SOD-activity in both mammalian and plant cells. 23 Here we have found, following the GUS staining protocol of Vitha et al, 24 increased DJ-1::GUS expression in root apices of Arabidopsis in response to short (30 min) blue light exposures (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that endogenous AtDJ-1 level in leaf was increased after treatment with stress factors, such as strong light, H 2 O 2 , methyl viologen and copper sulfate. 23 DJ-1 supports the cellular redox homeostasis by subserving a SOD-activity in both mammalian and plant cells. 23 Here we have found, following the GUS staining protocol of Vitha et al, 24 increased DJ-1::GUS expression in root apices of Arabidopsis in response to short (30 min) blue light exposures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 3D, we used GUS line of Arabidopsis DJ-1 (AtDJ-1) which was identified as a homolog of Human DJ-1 PARK7. 23 Mutation of human DJ-1 causes Parkinson's disease resulting in neuronal death. It was previously reported that endogenous AtDJ-1 level in leaf was increased after treatment with stress factors, such as strong light, H 2 O 2 , methyl viologen and copper sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Therefore, Enzyme assays revealed that AtDJ-1a and DJ-1 stimulated SOD/CSD1 activity and that only the copper-loaded forms of AtDJ-1a and DJ-1 had this effect suggesting that AtDJ-1a/DJ-1 may provide copper for SOD/CSD1. 11 Although the observed SOD activation provides clues towards the role of DJ-1 in detoxification of ROS, SOD only converts superoxide anion to H 2 O 2 which must further be detoxified to H 2 O by GPX and CAT. Although we showed that AtDJ-1a and human DJ-1 can interact with AtGPX2 and GPX2, respectively, we observed no changes in GPX2 activity upon DJ-1 interaction.…”
mentioning
confidence: 99%
“…The fact that Arabidopsis has three DJ-1 homologs where two of these, AtDJ-1b and AtDJ-1c, are localized to chloroplasts 11 underlines the protective has been elusive in terms of having a direct influence on neuronal cell death. 10 In an attempt to clarify the mechanism of DJ-1 we established Arabidopsis thaliana as a new and novel model system.…”
mentioning
confidence: 99%
See 1 more Smart Citation